UNLOCKING POTENTIAL: HOW SERUM L1EV Î‘-SYNUCLEIN MAY REVOLUTIONIZE PARKINSON'S DIAGNOSTICS - Zahid, Tabeer; Nabi, Rayyan; Farooqi, Hanzala Ahmed (Journal of Ayub Medical College Abbottabad, 2024)
Parkinson's Disease (PD) poses many challenges and the urgent need for early diagnosis, emphasizing the limitations of motor symptoms in providing timely detection is imperative. The MDS research criteria, including motor changes, non-motor symptoms, and dopaminergic functional imaging findings, are crucial markers for prodromal PD diagnosis. Shijun Yan et al. recent study introduces serum L1EV Î±-synuclein levels as a potential biomarker, detecting early pathogenesis shifts, serving as a cost-effective and accessible tool for screening high-risk individuals. The benefits of this multi-marker approach benefits in evaluating disease prognosis and progression. Serum L1EV Î±-synuclein's role in uncovering non-motor features, such as depression and anxiety, in prodromal PD underscores its significance for improving patient quality of life. The potential for early intervention using this biomarker offers hope for halting neurodegeneration and delaying clinical PD development. The global applicability of this promising biomarker needs to be looked into, while the need for more diverse racial and ethnic studies regarding it are required. Ultimately, the letter argues that identifying high-risk individuals through L1EV Î±-synuclein enables timely neuroprotective interventions, providing patients with valuable insights into disease progression and reducing uncertainty and fear.